GENDER AND SEXUALITY IN PHYSICAL EDUCATION: SCENERY, GAPS AND PERSPECTIVES (Fiep Bulletin - online, 2017)
The concern about the difficulties of implementation of the themes gender and sexuality in an emancipatoryperspective gestated in the practice with the current scenario of resurgence and advance of conservative ideas related to thetheme and that has directly impacted the school environment, limiting initiatives discussion, construction of knowledge andadvances of social practices. This study pursued the goal of identifying on scientific articles and preferred approaches underwhich has been structured research and studies developed in this area. This is a literature review that discusses the tenseinterface between gender issues, sexuality, health and education. From the Scielo database were selected academic articlespublished in the last decade in national journals from the field of education that address the themes gender and sexuality in theschool's strategic space. From the descriptors used, the articles found amounted incipient. The articles selected were classifiedinto: 1) Teachers and Students; 2) Pedagogic Proposals and Teacher Training; 3) Teaching Materials and 4) EpistemologicalStudies, and the tenor of the discussions pointed to the maintenance of a conservative view. It was found that although atransversal approach guidance, presented by the official guidelines for education, with a view to extended discussion andtransdisciplinary and thus, as na initiative in all areas, resulting in an initiative neglected by all, ending up constitute an obstacle,relegating the issue to silencing.
Keywords: Gender; Sexuality; Helth Promotion; School